Theoretical evaluation of adsorption desalination performance of metal-organic frameworks under varying scenarios. (October 2022) - Wang, Yichen; Xia, Xiaoxiao; Shen, Dongchen; Tu, Zhengkai; Luo, Xiaobing; Li, Song
Graphical abstract: Highlights: Adsorption desalination performance of 12 adsorbents was evaluated. MOFs outperform other adsorbents owing to their higher water transfer amount. Desalination performance of adsorbents is correlated with adsorption characteristics. DUT-67 is the most potential candidate under varying operation conditions. Abstract: Adsorption desalination systems (ADs) driven by low-grade energy are regarded as sustainable alternatives to address water shortages due to their low energy consumption. Adsorbents is the key materials for the performance of ADs. In this work, a numerical study was performed to assess the water production performance of ADs based on metal–organic frameworks (MOFs) and other adsorbents under different working conditions. It is found that the trends in specific daily water production (SDWP) and performance ratio (PR) with hot and chilled water temperature are closely correlated with the adsorption characteristics, i.e., water uptake and the shape of adsorption isotherms. Moreover, considering both SDWP and PR, MOFs outperform other adsorbents owing to their high water transfer amount per cycle under various conditions. Among 12 adsorbents, DUT-67, Al-fumarate and MIL-100(Fe) are the top performers at chilled water temperature of 10 °C, 20 °C and 30 °C respectively with average SDWP (PR) of 3.31 m 3 /ton/day (0.33), 8.05 m 3 /ton/day (0.56) and 13.46 m 3 /ton/day (0.71), increased by 43.8% (32.0%), 65.3% (40%), and 102.7% (44%) compared to traditional silica gel. This work provides helpful insights into the correlation between desalination performance and water adsorption characteristics of adsorbents under varying working conditions, which favors choosing and designing of potential adsorbents for ADs.